An Exploratory Analysis in Mapping of Asthma Risk in Western Australia - Hendra Kurnia Febriawan; Carla Maria da Silva Sodre (Faculty of Geography, Universitas Gadjah Mada, 2018)
Exploratory Analysis as one of the spatial analysis tools that has been used widely in many study fields. This tool is usually intended to obtain the spatial pattern to observe and get relationship between study variables. The exploratory analysis is usually followed by the confirmatory analysis to exhibit the hypothesis that already obtain in the exploratory analysis. This study is aimed to investigate the prevalence of asthma in Western Australia since there are many factors that cause the asthma dispersion. Many provided variables have been tested to get the best correlation with the asthma percentage variable and four variables (humidity, annual rainfall, EVI and SEIFA) were chosen and tested with high asthma percentage variable. The result of confirmatory analysis indicates that the high level of humidity and low level of SEIFA confirm with the hypothesis and means that those factors can contribute significantly in Asthma prevalence in Western Australia.